The Crisis, COVID-19 and the Acceleration of the Fourth Industrial Revolution - Prodanov, Hristo (Research Papers, 2021)
The study aims to analyze the Сovid-19 pandemic and the acceleration of digitalization as an essential feature of the Fourth Industrial Revolution. This aim determines the object of the research – the pandemic crisis, as well as its subject – the consequences it has on the digital revolution and the related changes in politico-economic system. The approach is politico-economic and systematic, examining the interaction of three groups of factors – technology, economics and politics in the transformation of the entire politico-economic system through the analysis of its subsystems. This approach addresses economic and pandemic crisis as the main factor of the acceleration of the socio-economic transformations, and then focuses on digitalization as the main mechanism for managing the pandemic, as well as its consequences for production, services, trade, distribution, consumption, labor, education, science, health and the state. An attempt is made for the first time to systematically analyze the pandemic of Сovid-19 and the acceleration of technological innovations, as well as the related transformation of the politico-economic system as a result of the contradictions caused by the rapidly changing productive forces and relations of production, necessitating the need for changes in the political superstructure of society.